The use of community radio to support local development efforts in Ethiopia: the case of Waghimra Community Radio - Mohammed, Jemal (Penerbit Universiti Kebangsaan Malaysia, 2018)
Currently, around 34 community radio broadcasters are operational in Ethiopia. Because community radio is a new media culture in Ethiopia, the main purpose of this study was to investigate to what extent Waghimra Community Radio has been successful in supporting local development efforts since its establishment. To serve the purpose of the study, quantitative method was employed. By using questionnaire, the necessary data were collected from all educated civil servants (426) who was working in Seqota town and available at the time of data gathering. A very brief interview was also conducted with the Head of the radio station. The analysis and interpretation of data show that a little more than 36% of respondents believed that Waghimra Community Radio served the local community to acquire fresh information while 54.7% of the respondents believed that the participation of the local people in managing the Station is inadequate. More than 51% of the respondents believed that it does not serve the public interest. The study has also concluded that local government has at least an indirect control on the Station. The study recommended that to ensure the editorial independence and the very basic ownership of the radio system, the Station Board needs to be restructured so that it can be controlled by members of ordinary people. Various organizations need to support the Station in order to resolve the constraints related to financial problems, technical breakdown and lack of manpower.